A Novel Nanosafety Approach Using Cell Painting, Metabolomics, and Lipidomics Captures the Cellular and Molecular Phenotypes Induced by the Unintentionally Formed Metal-Based (Nano)Particles - Alijagic, Andi; Scherbak, Nikolai; Kotlyar, Oleksandr; Karlsson, Patrik; Wang, Xuying; Odnevall, Inger; Benada, Oldřich; Amiryousefi, Ali; Andersson, Lena; Persson, Alexander; Felth, Jenny; Andersson, Henrik; et al. (Cells, 2023)
Additive manufacturing (AM) or industrial 3D printing uses cutting-edge technologies and materials to produce a variety of complex products. However, the effects of the unintentionally emitted AM (nano)particles (AMPs) on human cells following inhalation, require further investigations. The physicochemical characterization of the AMPs, extracted from the filter of a Laser Powder Bed Fusion (L-PBF) 3D printer of iron-based materials, disclosed their complexity, in terms of size, shape, and chemistry. Cell Painting, a high-content screening (HCS) assay, was used to detect the subtle morphological changes elicited by the AMPs at the single cell resolution. The profiling of the cell morphological phenotypes, disclosed prominent concentration-dependent effects on the cytoskeleton, mitochondria, and the membranous structures of the cell. Furthermore, lipidomics confirmed that the AMPs induced the extensive membrane remodeling in the lung epithelial and macrophage co-culture cell model. To further elucidate the biological mechanisms of action, the targeted metabolomics unveiled several inflammation-related metabolites regulating the cell response to the AMP exposure. Overall, the AMP exposure led to the internalization, oxidative stress, cytoskeleton disruption, mitochondrial activation, membrane remodeling, and metabolic reprogramming of the lung epithelial cells and macrophages. We propose the approach of integrating Cell Painting with metabolomics and lipidomics, as an advanced nanosafety methodology, increasing the ability to capture the cellular and molecular phenotypes and the relevant biological mechanisms to the (nano)particle exposure.
Keywords: Humans; lipidomika; Metabolomics; targeted metabolomics; inflammation; high-content screening (HCS); Lung; metabolomika; Phenotype; epitelové buňky; lidé; plíce; Lipidomics; Epithelial Cells; new approach methodologies (NAMs); fenotyp; additive manufacturing; multivariate analysis; nanoparticle emissions